Studi Etnobotani Tumbuhan Anti-Penyakit Kulit dalam Sistem Pengobatan Tradisional Masyarakat Desa Jeruk Purut, Pasuruan - Dewi Sofiatul Laili; Heni Refdiana; Najwa Rofisa Amelia; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to document and preserve local knowledge about the use of medicinal plants for skin diseases used by the community of Jeruk Purut Village, Pasuruan Regency. The research method used is a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. Key informants were determined using purposive sampling, followed by snowball sampling to expand information from additional informants. The data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results of the study identified 14 plant species from 11 families used by the community to treat skin diseases, including acne, tinea versicolor, dermatitis, scabies, and ringworm. Leaves are the most widely used part of the plant due to their secondary metabolite content, which is effective as an antibacterial, antifungal, and anti-inflammatory agent. Processing is done traditionally through pounding, boiling, cutting, grating, or heating, and applied by rubbing, sticking, compressing, or drinking. The conservation status of most species is classified as Not Evaluated, indicating limited data and the need for further research as a basis for assessing extinction risk. These findings emphasize the importance of preserving local knowledge and the need for further research to ensure the sustainable use of medicinal plants.